Convolution factorability of bilinear maps and integral representations - ERDOĞAN, EZGİ (ELSEVIER SCIENCE BV, 2018)
In this paper we consider a special class of continuous bilinear operators acting in a product of Banach algebras of integrable functions with convolution product. In the literature, these bilinear operators are called 'zero product preserving', and they may be considered as a generalization of Lamperti operators. We prove a factorization theorem for this class, which establishes that each zero product preserving bilinear operator factors through a subalgebra of absolutely integrable functions. We obtain also compactness and summability properties for these operators under the assumption of some classical properties for the range spaces, as the Dunford-Pettis property or the Schur property and we give integral representations by some concavity properties of operators. Finally, we give some applications for integral transforms, and an integral representation for Hilbert Schmidt operators. (C) 2018 Royal Dutch Mathematical Society (KWG). Published by Elsevier B.V. All rights reserved.
Keywords: Bilinear operators; Factorization; Zero product preserving map; Summability; Hilbert-Schmidt operators; Integral representation